Aboriginal Children and Their Caregivers Living with Low Income: Outcomes from a Two-Generation Preschool Program. - Benzies, Karen; Tough, Suzanne; Edwards, Nancy; Mychasiuk, Richelle; Donnelly, Carlene (Journal of Child & Family Studies, 2011)
The development of preschool children of Aboriginal heritage is jeopardized by the inter-generational transmission of risk that has created, and continues to create, social disadvantage. Early intervention programs are intended to mitigate the impact of social disadvantage. Yet, evidence of the effectiveness of these programs for children of Aboriginal heritage is limited. The purpose of this study was to examine the effects of a two-generation, multi-cultural preschool program on 45 children of Aboriginal heritage and their caregivers. We used a single-group, pretest (program intake)/posttest (program exit) design with follow-up when the children were 7 years old. We used an observational measure of child receptive language (Peabody Picture Vocabulary Test-III) and caregiver-reported measures of child development (Nipissing District Developmental Screen), risk for child maltreatment (Adult-Adolescent Parenting Inventory; AAPI), parenting stress (Parenting Stress Index; PSI), self-esteem (Rosenberg Self-Esteem scale; RSE), and life skills (Community Life Skills scale; CLS). Using paired t-tests we found statistically significant increases in child receptive language scores between intake and exit, and repeated-measures ANOVA showed that these improvements were maintained up to age 7 years. For caregivers, Pearson's correlations demonstrated that risk for child maltreatment, parenting stress, self-esteem, and life skills were stable over time. Results of this study suggest that children of Aboriginal heritage can benefit from participation in a two-generation, multi-cultural preschool program. Their caregivers may have received greater benefit if issues of intergenerational transmission of the negative influences of residential schools were addressed as part of programming.